Surgical Anatomy of the Basal Turn of the Human Cochlea as Pertaining to Cochlear Implantation. Issue 2 (February 2015) - Singla, Anjali; Sahni, Daisy; Gupta, Ashok Kumar; Aggarwal, Anjali; Gupta, Tulika
Abstract : Hypothesis: To study the morphometry of the human cochlea with special emphasis on its basal and turn and their implications for cochlear implantation. Background: Cochlear implantation is an established mode of treatment for patients with bilateral, profound sensorineural hearing loss. The intricate knowledge of the anatomy of the cochlea and its variations like unusual constriction of the cochlear lumen or dysmorphic cochlea is important for the success of cochlear implantation. Design: Forty nonpathologic formalin-preserved human temporal bones were microdissected to expose the medial wall of the tympanic cavity. After exposure of the cochlea, its widest transverse and vertical diameters were measured. The internal diameter of the basal turn of the cochlea was measured on 13 sites at every 30-degree interval. The outer wall length of the basal turn was also measured. Results: The mean ± standard deviation transverse and vertical diameters of cochleae were 8.06 ± 0.80 and 5.85 ± 0.72 mm, respectively. The mean diameter of the basal turn gradually tapered from 1.98 ± 0.34 mm at 0 degrees to 1.21 ± 0.32 mm at 360 degrees. Unusual constrictions were observed in the basal turn of the cochlea in 3 cases (7.5%). A wide range was found in the outer wall length of the basal turn of the cochlea (range 15.6–24.6 mm). Conclusions: The cochleae differed significantly in their dimensions. Unusual constrictions found in the basal turn of the cochlea in 7.5% cases may explain the difficulties experienced by surgeons to reach full insertion in such cases. An extensive range (15.6–24.6 mm) of the length of the basal turn denotes significant variations of insertion degrees at constant surgical depths. The refined morphometric information of the cochlea may help in designing and selecting the electrode array for cochlear implantation.